Socio-demographic and clinical profile of patients with diabetic foot in a specialized outpatient clinic (Research, Society and Development, 2022)
Diabetes Mellitus is an expanding public health problem, so its projections are for growth in the coming decades. Among the main complications caused by this syndrome is the diabetic foot, which is characterized by several anatomical and physiological changes in the feet. The objective of the study was to analyze the sociodemographic and clinical profile of patients with diabetic foot who are treated at a specialized outpatient clinic in the city of Teresina, Piauí. The study is characterized as a descriptive field research with a quantitative approach through the application of an online questionnaire in Google Forms structured with objective questions directed at patients who live with diabetic foot treated at a specialized outpatient clinic. The study sample consisted of 15 (n=15) patients with a mean age of 54.7 years, predominantly male n=10 (66.7%), married marital status n=8 (53.3%) brown skin color n=12 (80%), origin from the capital n=8 (53.3%), incomplete primary education n=5 (33.3%) and income from one to three minimum wages n=12 (80 %). The research data showed a profile similar to that of studies developed in which the mean age of the patients was 63.2 years, statistical predominance of male patients, married and from the metropolitan region, type 2 diabetes mellitus and use of hypoglycemic medication oral. The occurrence was higher in males, aged over 38 years, predominating patients with little education, low income, with type II diabetes and who use oral hypoglycemic medication.